COVID-19 infection: neurological symptoms and encephalitis - A. Jasionis; R. Mameniškienė (Neurologijos seminarai)
In the height of COVID-19 pandemic, there is growing amount of data on neurological manifestations of the disease. They can be caused by a serious medical condition, acute neurological injuries or exacerbation of chronic neurological disorders, and adverse effects of antiviral therapies. Moreover, first reports of suspected encephalitis cases also appear. This article discusses published data on neurological manifestations of COVID-19 and their possible explanation, and presents reported encephalitis cases. Brain injury caused by other coronaviruses is also examined. Finally, we discuss the possible mechanisms by which the virus can enter the brain and cause injury.